Calcific tendonitis of the quadriceps. Issue 7 (23rd June 2006) - Varghese, B; Radcliffe, G S; Groves, C
Abstract : The case reported is of a 46 year old male who presented with a history of acute on chronic knee pain. The clinical features and investigations suggested a tear of the quadriceps tendon, with pre-existing chronic calcific enthesopathy. The operative findings were of an acute collection of calcific material within the quadriceps tendon. This acute presentation and calcific collection have not previously been reported in the quadriceps tendon.